Analysis of Factors Causing Compassion Fatigue in Nurses - Sulistiyowati, R. R. Woro; Suprapti, Fitriana (GoAcademica Research & Publishing, 2025)
Compassion fatigue can lead to behaviors such as loss of caring and compassion, thereby reducing the quality of care and ultimately failing to achieve the goal of improving patient health and unstable patient satisfaction. The purpose of this review was to identify and summarize published reviews on compassion fatigue in nurses and its impact on patient care. Three databases were searched, namely PubMed, Wiley Online Library, Proquest for studies on compassion fatigue in nurses, published in English from 2021 to 2024. The review used the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) extension to include articles. Of the 179 search results, 15 met the inclusion criteria. Several factors were identified in this review including burnout, number of dependent children, lack of task completion, nurse competence, nurse shift schedules, male nurse coping, low nurse income, low compassion satisfaction. This scoping review provides important insights into common causes and potential risks of compassion fatigue among nurses and identifies potential strategies to support nurses’ psychological health and well-being.